Recognition, clinical diagnosis and management of patients with primary antibody deficiencies: a systematic review. - Wood, P; Stanworth, S; Burton, J; Jones, A; Peckham, D; Green, T; Hyde, C; Chapel, H (2007)
The primary purpose of this systematic review was to produce an evidence-based review of the literature as a means of informing current clinical practice in the recognition, diagnosis and management of patients with suspected primary antibody deficiency. Randomized controlled trials (RCTs) were identified from a search of MEDLINE, EMBASE, The Cochrane Library, DARE (CRD website) and CINAHL by combining the search strategies with The Cochrane Collaboration's validated RCT filter. In addition, other types of studies were identified in a separate search of MEDLINE and EMBASE. Patients at any age with recurrent infections, especially in the upper and lower respiratory tracts, should be investigated for possible antibody deficiency. Replacement therapy with immunoglobulin in primary antibody deficiencies increases life expectancy and reduces infection frequency and severity. Higher doses of immunoglobulin are associated with reduced infection frequency. Late diagnosis and delayed institution of immunoglobulin replacement therapy results in increased morbidity and mortality. A wide variety of organ-specific complications can occur in primary antibody deficiency syndromes, including respiratory, gastroenterological, hepatic, haematological, neurological, rheumatological and cutaneous. There is an increased risk of malignancy. Some of these complications appear to be related to diagnostic delay and inadequate therapy. High-quality controlled trial data on the therapy of these complications is generally lacking. The present study has identified a number of key areas for further research, but RCT data, while desirable, is not always obtained easily for rare conditions. Few data from registries or large case-series have been published in the past 5 years and a greater focus on international collaboration and pooling of data is needed.